Sosialisasi Peningkatan Kualitas Hidup Masyarakat Dalam Kelompok Kerja Kampung Keluraga Berkualitas (KB) di Desa Sadananya - Andi Sunardi; Irfan Nursetiawan; Muhammad Fariz; Ranti Lestari; Vina Dwi Yulianti (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
The Quality Family Village (KB) program aims to improve the quality of life of the community through empowerment and outreach that focuses on various aspects of life. This research examines the effectiveness of socialization in improving the quality of life of the community in the KB Village working group. The method used is descriptive qualitative, collecting data through observation, in-depth interviews and document analysis. The research results show that effective socialization involves active community participation, delivery of clear and easy-to-understand information, and support from various parties, including the government and non-government organizations. The conclusion of this research confirms that through structured and systematic socialization, people's quality of life can be improved, especially in health, education and economic aspects. Recommendations are provided to expand the reach of the program and increase the involvement of all elements of society for more sustainable success.